Carl Schmitt’s Political Theology of Revolution - Herrero López, Montserrat (Open theology, 2023)
Is there a political theology of revolution in Carl Schmitt or is his political theology only and exclusively autocratic? Schmitt sees the key to revolutionary politics in the construction of the idea of the people as a constituent power. This idea, and the first event it produced, namely, the French Revolution, not only establishes a concrete state of exception but also makes exceptionality both at the same time a constituent and a de-constituent element of the political order of the Modern State. The exception goes from coming from "outside" the political order to being integrated into it as an element of stasis , that is to say, of destabilization. Hence, all modern politics, under the mask of legality, become permanently revolutionary. This article analyses the juridical genealogy and the theological-political transfers involved in the construction of the modern revolutionary political era that follows from Schmitt’s insights.